PENGARUH BUDAYA ORGANISASI, KEPEMIMPINAN, DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. PELABUHAN INDONESIA III (PERSERO) CABANG TANJUNG EMAS SEMARANG - Rahdita, Rayyan -; Riyanto, Makmun -; Utaminingtyas, Rara Ririnbudi (Politeknik Negeri Semarang, 2016)
The purpose of this reseach was to identifythe influence of organizational culture,leadership and working motivation toemployee’s satisfaction at PT. PelabuhanIndonesia III (Persero) Branch Tanjung EmasSemarang. Questionnaire, Interview andliterature studies were the instruments to useto collect data. Questionnaires weredistributed to 60 employee’s as respondents.The data analysis used the method of multiplelinier regression coefficient analysis.Regression analysis was used to determinethe influence of organizational culture,leadership and working motivation toemployee’s satisfaction. Data were processedusing SPSS v.17.0. The result of this study isthat the calculation of regression coefficientobtained Y = 1,585 +0,270X1 + 0,197X2+0,340 X3 It meant that result of regressiongave positive influence on employee’ssatisfaction, and the influence of workingmotivation was greater than the othervariables.The result of t-test, tcount value ofculture organization was 2.723, leadershipwas 2.611, working motivation was 3.096.and ttable value was 1.673. from these resultmay be known the tcount> ttable so Ha accepted,which meant that partial test of organizationculture. leadership, and working motivationhad positive effect for workingsatisfaction.The result of F-test, Fcount value oforganization culture, leadership, and workingmotivation was 47.392 and Ftable value was2.796, value of Fcount> Ftable so Ha would beaccepted, which meant that simultaneouslyorganizational culture, leadership danworking motivation had positive effect onemployee’s satisfaction. The coefficient ofdetermination was 0,702. It meant that theemployee’s satisfaction of 70,2% wasinfluenced by organizational culture,leadership and working motivation, while therest of 29,8% was influenced by the otherfactors.